The Role of Collectivism–Individualism in Attitudes Toward Compliance and Psychological Responses During the COVID-19 Pandemic - Xiao, Wen S. (Frontiers in Psychology, 2021)
This study examined the role of individual differences in horizontal and vertical individualism and collectivism, trust and worries and concerns about COVID-19 in predicting the attitudes toward compliance of health advice and psychological responses during the COVID-19 pandemic. Chinese university students (N = 384, 324 female) completed measures of individualism and collectivism, trust, attitudes toward compliance and psychological responses to the pandemic. Results showed that not only vertical collectivist orientation but also horizontal individualist orientation significantly predicted higher willingness to comply, whereas vertical individualist orientation significantly predicted lower willingness to comply. Vertical individualist and vertical collectivist orientations predicted higher psychological response in terms of distress, anxiety, and depression, while horizontal collectivistic orientation significantly predicted less psychological problems. Implications of the effect of individual-level cultural orientations on attitudes toward public health compliance and psychological well-being during global health crises are discussed.